IMF Staff papers, Volume 44 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1997)
This paper studies the case of Mexico to examine determinants of banking system fragility. The paper tests empirically the proposition that bank fragility is determined by bank-specific factors, macroeconomic conditions, and potential contagion effects. The methodology allows the variables that determine bank failure to differ from those that influence banks' time to failure (or survival rate). Based on the indicators of fragility of individual banks, the paper constructs an index of fragility for the banking system. The framework is applied to the Mexican financial crisis that began in 1994.